Pengembangan DPAL untuk Kreativitas Guru Bahasa Arab di Era Kurikulum Merdeka - Novel Novel; Ahmad Munjin Nasih (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the influence of innovation and creativity in digital Arabic language learning, identify research gaps related to digital integration and self-directed learning pedagogy, and formulate a theoretical model for Digital Project Arabic Language Learning (DPAL), which combines technological innovation, teacher creativity, and the principle of learner autonomy. This research method uses library research. The results of this study propose an Arabic language curriculum design using the DPAL model, which can serve as a blueprint for religious education departments to develop digital, creative, and project-based Arabic language curricula. Theoretically, this study provides a conceptual framework for DPAL in Arabic language teaching. The gap identified by the researcher is the integration of the Independent Curriculum paradigm into the digital-based Arabic language learning design for its systematic implementation.